CHANGES IN SOCIAL VALUES IN MULTICULTURAL SOCIETIES A COMPARATIVE STUDY BETWEEN GENERATIONS - Ida Farida (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This research aims to analyze changes in social values in a multicultural society through a comparative study between generations, based on a comprehensive literature review. In the context of globalization and increasing social mobility, social values tend to undergo significant transformation from one generation to the next. This literature review explores how values such as tolerance, coexistence, inclusion, and cultural identity are perceived and implemented by the older generation compared to the younger generation. The research results show that the younger generation tends to be more open to cultural diversification and more adaptive in integrating new values, while the older generation often maintains traditional values, but still shows the ability to adapt in the face of social change. This research concludes that intergenerational dialogue and multicultural education are the main keys in creating social harmony and reducing the potential for value conflict in a multicultural society. With a deep understanding of the dynamics of changing social values between generations, social policies and strategies can be more effective in supporting sustainable social integration and cohesion.